PEMIKIRAN TENTANG PENERJEMAHAN KOLABORATIF - Aveling, Harry (Jurnal Penerjemahan, 2014)
This article deals with the potentials and problems of co-translation, the production of a target text by two people: one who knows the source language and another who does not. It argues that the processes of translation and co-translation are identical once a preliminary initial target text translation (a "crib") has been established. Drawing on debates relating particularly to the translation of North American Indian texts during the 1980s, it calls for faithfulness to the original sourcetext and also for the "duty of disclosure", through which the translators explain to the new readership their aims, methods of working, and how they have dealt with the various problems they have faced in producing the new target text together.